The Effect of Nimodipine on Nuclear Factor Erythroid-2-Related Factor 2 (Nrf2) Activation in Neuron Cell Line SH-SY5Y Culture Exposed By Chronic Hyperglycemia - Shahdevi NK (Journal of Global Pharma Technology, 2016)
Introduction: Diabetes is a dysregulation of glucose metabolism due to defects in insulin secretion, decreased insulin sensitivity, or a combination of both that causes hyperglycemia. Diabetic neuropathy is induced by oxidative stress that results from excessive ROS production. When oxidative stress increases, it triggers a transcriptional response of antioxidant genes mediated by Nrf2. Based on the above mechanism, the researchers tried to use nimodipine as a calcium channel blocker which is neuroprotective to reduce Nrf2 activation. Objectives: This study aims to look at the effect of nimodipine on decreasing Nrf2 activation. Methods: This research was conducted in vitro using SH-SY5Y neuron cell culture induced hyperglycemia for 6 days with glucose concentrations of 5 mM, 25 mM, and 50 mM. Then the cell is harvested and given nimodipine for 30 minutes at a dose of 10 nM and 100 nM. Nrf2 expression was observed under a confocal microscope. Results: The results of nimodipine at doses of 10 nM and 100 nM were able to reduce the activation of Nrf2 in neuron cell culture that had been significantly induced by chronic hyperglycemia (p <0.05) at 50 mM glucose concentration. Conclusion: It can be concluded that the administration of nimodipine doses of 10 nM and 100 nM can reduce Nrf2 activation in neuron cell cultures exposed to chronic hyperglycemia with glucose concentrations of 50 Mm.Keyword: Hyperglycemia, SH-SY5Y Cell, Nimodipine, Nrf2.